Prevalence and antimicrobial susceptibility of Acinetobacter spp. isolated from meat - Carvalheira, Ana (2017)
The prevalence and antibiotic resistance of Acinetobacter spp. from fifty samples of meat (chicken, turkey, beef and pork) were evaluated. Acinetobacter spp. was recovered from all samples and the clonal relatedness of 223 isolates identified to belong to the genus Acinetobacter was established by PFGE. A high genetic diversity was observed and 166 isolates from different samples, 141 representing different PFGE profiles, were further identified to the species level by rpoB gene sequencing. Thirteen distinct Acinetobacter species were identified among 156 isolates. The remaining ten isolates may represent three putatively novel species since rpoB sequence homologies with type strains of all available described Acinetobacter species, were <95%. The most common species was Acinetobacter guillouiae with a prevalence of 34.9%. However 18.7% of the strains belong to the Acinetobacter baumannii group (n=31) which include the species Acinetobacter baumannii (n=7), Acinetobacter pittii (n=12), Acinetobacter seifertii (n=8) and Acinetobacter nosocomialis (n=4) that are the species most frequently associated with nosocomial infections worldwide. In general, strains were resistant to some of the antimicrobials most frequently used to treat Acinetobacter infections such as piperacillin-tazobactam (64.9% of strains resistant), ceftazidime (43.5%), ciprofloxacin (42.9%), as well as to colistin (41.7%) and polymyxin B (35.1%), the last-resort drugs to treat infections caused by multidrug-resistant Acinetobacter. The percentage of resistant strains to trimethoprim-sulfamethoxazole, tetracycline, aminoglycosides (amikacin and tobramycin) and ampicillin-sulbactam was >10% (23.2%, 23.2%, 14.3%, 12.5%, 12.5%, respectively). However, resistances to meropenem, imipenem and minocycline were only sporadically observed (8.3%, 1.2% and 1.2%, respectively). Overall, 51.2% of the strains were considered as multidrug-resistant (MDR) and 9.6% as extensively drug-resistant (XDR). The prevalence of MDR strains within the A. baumannii group (38.7%) was lower than the prevalence within the others species identified (54.1%). Therefore, food of animal origin may be a vehicle of spread Acinetobacter strains resistant to several antibiotics in the community and in the hospital setting environment. This may led to nosocomial and community-acquired infections in susceptible individuals.